RESPON GALUR/VARIETAS KAPAS (Gossypium hirsutum L.) TERHADAP PUPUK DOSIS N dan ZAT PENGATUR TUMBUH PADA SISTEM TUMPANGSARI DENGAN JAGUNG - Fitriningdyah Tri Kadarwati; Prima Diarini Riajaya (BERITA BIOLOGI, 2016)
Cotton lines/varieties with high productivity require high availability of nutrients in the soil, especially nitrogen (N). To maximize the utilization and distribution of nutrients in the crops, plant growth regulator (PGR) is needed to optimize the cotton production. The research was aimed to estimate the suitable dose of N fertilizer and plant growth regulator suitable for the new cotton lines. The experiment was conducted in Mojomulyo village, Tambakromo District, Pati, Central Java, from May to October 2011.  The research was arranged in a Split Plot Design with three replications. The main plots were three lines/varieties of cotton: 99022/1; 99023/5 and Kanesia 13. The subplots were sixdose  of combination of N fertilizer with PGR namely (1) N 90 + mepiquat chloride; (2) N 90 + pachlobutrasol; (3) N 90  without PGR; (4) N 120 + mepiquat chloride; (5) N 120 + pachlobutrasol; and (6) N 120  without PGR. The results showed that under drought conditions, the use of PGR pachlobutrasol was better than mepiquat chloride. Pachlobutrasol has a higher impact on cotton production with high N fertilization (120 N/ha) resulting in 701.26 kg cotton/ha. When mepiquat chloride was added cotton production reached 665.37 kg/ha and 604.81 kg/ ha with no PGR. Production of cotton lines 99023/5 was 721.65 kg/ha higher that of Kanesia 13 (577,50 kg/ha).